Mapping Unsafety Driving Zone on Trans Semarang Corridor VI to Improve Public Transport Service. (August 2019) - Basuki, Y; Rahayu, S; Nino, B
Abstract: The concept of sustainable transportation has become an agenda for urban areas in both developed and developing countries. One of the implementations in realizing the concept of sustainable transportation is the development of mass public transportation facilities. Bus Rapid Transit (BRT) is one of the modes considered suitable for developing cities such as Semarang named Trans Semarang. To ensure the sustainability of the BRT, good planning and operation and maintenance are required. In the operation of BRT safety driving behaviour is believed to make the BRT safe and reliable for passenger. This research is intended to know the behaviour of the driver in operating the BRT. From driver's behaviour and onboard survey can be classified the level safety driving the operation of BRT in Semarang. Safety driving level assessment was conducted on a sample of the BRT fleet. The analysis is done by making the level of safety driving divided into high, medium and low. At medium and low level, it can be said un safety driving and conducted analysis of the cause. Furthermore, spatial analysis is done to map the areas that have low levels. From the mapping results can be concluded which areas have medium and low safety driving level and what causes it. From these conclusions, recommendations for BRT performance improvement can be formulated